2019
DOI: 10.1021/acssuschemeng.9b02519
|View full text |Cite
|
Sign up to set email alerts
|

CuS Nanosheets Decorated with CoS2 Nanoparticles as an Efficient Electrocatalyst for Enhanced Hydrogen Evolution at All pH Values

Abstract: The design and fabrication of eco-friendly, highly efficient, and non-noble-metal-based catalysts are demanding challenges in energy-conversion technologies. Herein, we successfully synthesized CuS nanosheets decorated with CoS2 nanoparticles through a facile route. The optimized 3% CoS2-7% CuS catalysts exhibited remarkable electrocatalytic performance, with excellent cyclic stability at all pH values for the hydrogen evolution reaction (HER). They exhibited lower Tafel slopes (46, 52, and 59 mV dec–1) and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…[ 60 ] For S 2p spectra, the corresponding peaks are found at 160.5 and 161.6 eV, which is assigned to the S 2p 3/2 and S 2p 1/2 of S 2− in metal sulfides. [ 61 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 60 ] For S 2p spectra, the corresponding peaks are found at 160.5 and 161.6 eV, which is assigned to the S 2p 3/2 and S 2p 1/2 of S 2− in metal sulfides. [ 61 ]…”
Section: Resultsmentioning
confidence: 99%
“…26 There are many recent works on Cu x S y applications in the newly emerging research fields created by the current economic and environmental issues, such as solar cells, photovoltaics, photocatalysts, photothermal agents, and electrocatalysts for the HER and CO 2 reduction reactions. [30][31][32][33][34][35][36][37][38] A few studies were performed to explore the applicability of Cu x S y for the HER and CO 2 reduction, which revealed that Cu-based materials could be used in energy storage devices and major CO 2 converters. 30,[39][40][41] In most previous works, Cu x S y was prepared by a conventional hydrothermal method, chemical bath deposition, and wet-chemical route.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cu 2 S does not exhibit any localized surface plasmon resonance (LSPR) 26 . There are many recent works on Cu x S y applications in the newly emerging research fields created by the current economic and environmental issues, such as solar cells, photovoltaics, photocatalysts, photothermal agents, and electrocatalysts for the HER and CO 2 reduction reactions 30‐38 . A few studies were performed to explore the applicability of Cu x S y for the HER and CO 2 reduction, which revealed that Cu‐based materials could be used in energy storage devices and major CO 2 converters 30,39‐41 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the properties of electrochemical devices are closely related to the structure of materials. Therefore, in recent years, scientists have been trying to develop new techniques for synthesizing different structures such as nanoparticles, nanosheets, nanocrystals, nanoboxes, , nanowires, and so on. Nonetheless, the performance of pure CoS 2 is still insufficient due to lack of active sites and low conductivity.…”
Section: Introductionmentioning
confidence: 99%